Analisis Semiotika Roland Barthes pada Video Musik Exo Lotto - Rahma Rezqita Arum; Radea Yuli A Hambali (Gunung Djati Conference Series, 2023)
This study aims to discuss Roland Barthes' semiotic analysis of the Exo Lotto Music Video. The research method used is a qualitative descriptive type through observation techniques and library research. The results and discussion of this study are that there are signs of denotation, connotation, and myths in the Exo Lotto music video. This music video with a black concept that dominates tells about freedom, money and gambling. Where gamblers spend a lot of money on bets, but after that it's all ruined.